2005
DOI: 10.1108/09604520510585370
|View full text |Cite
|
Sign up to set email alerts
|

The importance of attitude and appearance in the service encounter in retail and hospitality

Abstract: For service organisations the interaction between front-line personnel and the customer is crucial as they aim to create high quality service encounters. Much research has focused on attempts by organisations to inculcate the "right" kind of attitude in their front-line employees. This paper seeks to extend this analysis by pointing to the increasing importance not just of having employees with the "right" attitudes, but also possessing aesthetic skills. The emergence of aesthetic skills reflects the growing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
228
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(251 citation statements)
references
References 20 publications
(22 reference statements)
9
228
1
2
Order By: Relevance
“…This is obviously the case in the sex industry (Hakim, 2012;Voracek & Fisher, 2006) and in much of the entertainment industry (Dean, 2005). Nickson, Warhurst, and Dutton (2005) suggest that this is also the case in retail and hospitality. They note, for example, how requirements for attractiveness in the retail and hospitality industries are often signalled through the use of phrases like 'well-spoken' (interpersonal skill) or 'well turned-out' (aesthetic presentation) in job advertisements and policed through requirements to submit photos with job applications (beauty).…”
Section: Why Does Career Image Confer Such Benefits?mentioning
confidence: 99%
“…This is obviously the case in the sex industry (Hakim, 2012;Voracek & Fisher, 2006) and in much of the entertainment industry (Dean, 2005). Nickson, Warhurst, and Dutton (2005) suggest that this is also the case in retail and hospitality. They note, for example, how requirements for attractiveness in the retail and hospitality industries are often signalled through the use of phrases like 'well-spoken' (interpersonal skill) or 'well turned-out' (aesthetic presentation) in job advertisements and policed through requirements to submit photos with job applications (beauty).…”
Section: Why Does Career Image Confer Such Benefits?mentioning
confidence: 99%
“…Such a perception of tourism and hospitality employment is not only inaccurate but also creates a negative image of the industry. A study by Nickson et al (2005) conducted in Glasgow in the retail and hospitality industries confirm the importance of 'soft skills'. They revealed that employers look for skills which encompass the social, interpersonal and aesthetic skills that are related to appearance.…”
Section: Inmentioning
confidence: 99%
“…Public opinion generally associates being healthy with being thin, such that being thin seems normative for citizens and employees (Madden & Chamberlain, 2010;Nickson, Warhurst, & Dutton, 2005;Smeesters, Mussweiler, & Mandel, 2010), though the gap between this cultural norm and biological reality is widening (D'Alessandro & Chitty, 2011). Many overweight or obese people regularly suffer from social stigma and personal dissatisfaction (Dehghan, AkhtarDanesh, & Merchant, 2005;Madden & Chamberlain, 2010).…”
Section: Literature Review Healthy Eating As Social Normmentioning
confidence: 99%
“…Then they consume their meals in the presence of strangers, including other guests and service employees. Several studies suggest that overweight people can have negative influence on others' food choice behaviors (e.g., Christakis & Fowler, 2007;McFerran et al, 2010aMcFerran et al, , 2010b, leading to further stigmatization and even discriminatory hiring practices that select employees on the basis of their appearance (e.g., Nickson, Warhurst, & Dutton, 2005;Warhurst, van den Broek, Hall, & Nickson, 2009). Warhurst et al (2009) note that employees' looks are increasingly important in interactive service jobs and caution that it might be the "next frontier in the struggle against discrimination in employment" (p. 132).…”
mentioning
confidence: 99%